Discrete SnO2 Nanoparticle‐Modified Poly(3, 4‐Ethylenedioxythiophene):Poly(Styrenesulfonate) for Efficient Perovskite Solar Cells. Issue 10 (15th October 2019) - Jia, Pengcheng; Bi, Wentao; Huang, Xin; Li, Ling; Gong, Wenwen; Tang, Yang; Zhao, Di; Hu, Yufeng; Lou, Zhidong; Teng, Feng; Cui, Qiuhong; Hou, Yanbing
Abstract : Interface Modification Engineering In article number19000162, Qiuhong Cui, Yanbing Hou, and co‐workers construct perovskite solar cells with discrete SnO2 nanoparticle‐modified layers by spin coating the SnO2 dispersions on PEDOT:PSS. The discrete SnO2 nanoparticle film lets holes pass and block electrons to diffuse toward PEDOT:PSS, which enhances the extraction efficiency, leading to an increase in power conversion efficiency.